Pengaruh Permainan Tradisional Engklek dan Permainan Puzzle terhadap Kemampuan Sosial Emosional Anak Usia Dini (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
This study aims to determine the effect of traditional engklek and puzzle games on the social-emotional abilities of early childhood in Kindergarten IT DOD Medan. This type of quantitative descriptive research uses a quasi-experimental design with a pretest and posttest experimental control group design. The population in the study were all students at TK IT DOD Medan, totaling 55 students with a sample of 43 students. Each was divided into three groups—data collection methods using observation and emotional social checklist sheets for early childhood with a scale rating scale. Based on the results of the data analysis carried out, the following research results were obtained: a) the traditional crank game has an effect on the development of social-emotional abilities of early childhood in Kindergarten IT DODO Medan with an N-Gain Score of 0.5921, b) puzzle games have an influence on the development of abilities social-emotional early childhood in Kindergarten IT DOD Medan with N-Gain Score o.6219, c) Then there is the effect of differences in traditional crank games and puzzle games on social-emotional abilities of early childhood in Kindergarten IT DOD Medan with an N-Gain Score difference of 0.0298. So it can be seen from crank and puzzle games that puzzle games are more influential in improving early childhood social-emotional abilities in Kindergarten DOD Medan.